Studi In-Vivo Ekstrak Daun Teh Hijau (Camellia Sinensis) sebagai Alternatif anti Bakteri Eschericia Coli pada Ayam Broiler - Bambang Sutrisno; R. Wasito; Kurniasih Kurniasih; Sitarina Widyarini; Yuli Purwandari Kristianingrum; Sugiyono Sugiyono (Jurnal Sain Veteriner, 2019)
The prevalence of colibasillosis  in chicken farms in Indonesia is very high, treatment using antibiotics is experiencing resistance, so it is necessary to look for alternatives to antibacterial. The study was aimed to determine the antibacterial effect of green tea leaf extract on broiler chickens infected with Eschericia coli by looking at the score of macroscopic lesions strengthened by histopathological examination, heterophile examination, plasma protein and fibrinogen. The research used 20 day old broilers (DOC) which were randomly divided into 4 groups, group A group B, group C and group D, each consisting of 5 DOC broilers. While maintaining ND and Gumboro vaccines on schedule like maintenance in general. At the age of 21 days all broilers in each group began to be treated as controls (Group A) without infecting E. coli and were not given 0,1g/ml  water extract of green tea leaves (Camillia sinensis). Group B, intratracheal-infected broilers with local strains of E.coli were 108 cells / ml according to 0,5  Mc Farland standard, and were not given green tea leaf extract. Group C, broilers infected by intratracheal with local strains of E. coli 108 cells / ml by 0,5 Mc Farland standard, and given to drink green tea leaf extract (Camillia sinensis) 0,1 g/ml and group D, broilers were given drinking green tea leaf extract (Camillia sinensis) 0,1g/ml. During the treatment all of chickens were given food and drink ad libitum. Fourteen days after infection of E.coli, 5 chickens in each group were collected to collect blood for heterophyll, total plasma protein (TPP) and fibrinogen. And then were euthanasied  with Mg SO4 saturated solution intravenously injection and necropsied  for gross and histpathological examination. Analysis of blood tests results were used one way of anova  (SPSS version 22 program), whereas for gross and histopathological examination with descriptive analysis. The results showed that the gross examination and histopathological organs of brolier infected with E. coli without being given a green tea extract experienced airsacculitis, pericarditis, perihepatitis and peritonitis, whereas broilers infected with E. coli and given green tea extract does not indicate the presence of inflammation. Examination of heterophile counts and blood fibrinogen levels had shown a difference (P <0.05), in broilers infected with E. coli and given green tea extracts had lower amounts of hetrophils and fibrinogen levels. While blood TPP levels were not significantly different (P> 0.05). The conclusion can be drawn, that the study of in vivo green tea extract (Camelia sinensis) 0,1g/ml has the potential to inhibit the infection of Eschericia coli bacteria in broiler chickens.